Sustainability in Coffee Shops: A Triple-Layered Business Model Canvas Approach - Rasyd, Muhamad Rafi Abdul; Mulyadi, Hari; Utama, Dian Herdiana; Furqon, C; Twum, Silas (Research Synergy Foundation, 2025)
This study examines how coffee shops in Bandung implement the Triple Layered Business Model Canvas (TLBMC) to balance profitability with ecological stewardship and social responsibility. Its primary aim is to simultaneously highlight the core factors enabling such establishments to thrive within economic, environmental, and social dimensions. Employing a qualitative method, the research collects data from interviews and detailed on-site observations. The findings indicate that revenue diversification and efficient resource management result in economic benefits, while environmentally conscious initiatives such as local sourcing, composting practices, and reusable packaging reduce costs and enhance public image. Social engagement through staff development programs, community events, and transparent supply chain practices fosters greater customer loyalty and a positive brand reputation. The synergy among these three layers demonstrates the potential of the TLBMC framework to support holistic value creation, even for small-scale enterprises with limited resources. In conclusion, the study provides practical evidence that adopting a TLBMC-centered strategy can yield multiple tangible and intangible gains, thereby encouraging broader sustainability transformations in local coffee shop contexts. These findings underscore the value of integrating economic, environmental, and social considerations as a cohesive framework for fostering long-term business resilience and community well-being. However, this study is limited to coffee shops within a single urban context, which may reduce the generalizability of the findings. Future research could expand the geographical scope or employ longitudinal designs to strengthen the study’s broader applicability.